The effect of compensation, work environment and work satisfaction toward employees performance at Regional Hospital of Prambanan - Muhammad Aditya Nugroho (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2020)
Efforts to improve the quality of a hospital should consider how job satisfaction of medical personnel, which will later have an impact on medical personnel performance. There are various ways that will be taken to improve performance, for example by providing appropriate compensation and improving quality of work environment conditions. Then job satisfaction is expected to increase and have a good impact on medical personnel performance at a hospital. The purpose of this study was to determine the effect of compensation, work environment and job satisfaction with employee performance at Prambanan Regional Hospital. This study used four variables namely compensation, work environment, job satisfaction and performance. The population in this study was employees who worked at Prambanan Regional Hospital, amounting to 300 people. The sampling technique used simple random sampling with a research sample of 150 people. Data analysis techniques used Structural Equation Modeling analysis. The result shows that there is a positive an significant effect between the compensation on the employee job satisfaction; there is a positive and significant effect between the work environment on the employee job satisfaction; there is a positive and significant effect between the compensation on the employee performance; there is a positive and significant effect between the work environment on the employee performance; there is no effect of the job satisfaction on the employee performance; satisfaction does not mediate the effect of compensation on the employee job satisfaction at Prambanan Regional Hospital.